News innovation through infotainment in the 'Meet Nite Live' program on Metro TV news television - Iman Indrati (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2024)
Innovation in delivering news programs with a newstainment style is one alternative to increase audience retention. This study aims to describe the newstainment Meet Nite Live through multimodal analysis, analyze editorial considerations in producing news in newstainment format, interpret news innovation based on newstainment, and analyze the impact of newstainment on journalistic values. The research methodology uses a qualitative descriptive approach, indepth interview, and multimodal discourse analysis. The results of the study, the application of new newstainment innovation, present attractive visuals, flexible urban language, and casual gestures; news is packaged sensationally with an emotional approach, and the use of clickbait reflects the shift from conventional journalism to popular journalism. Editorial considerations adjust the information needs of the digital community by presenting educational information and upholding the press as part of the pillars of democracy. Newstainment innovation in Meet Nite Live presents news with a light and entertaining delivery and still upholds journalistic principles. This study strengthens the theory of media convergence by proving that newstainment can attract young audiences without ignoring journalistic ethics. The findings contribute to the media in developing interactive but accurate news content. Further research could expand the sample and examine the psychological-cognitive impact of newstainment.